A statistical method of forecasting the movement of cyclonic storms in the Bay of Bengal - BANSAL , R. K.; DATTA, R. K. (MAUSAM, 1974)
Arakawa (1963) established a set a of regression equations to forecast the movement and the central pressure of typhoons in the western North Pacific. In the present paper, using a similar scheme, we have fitted two sets of regression equations, one each for the pre-monsoon and post monsoon seasons (1963 to 1970). These equations have been tested during the storm season of 1971 and the results, which are encouraging, are presented in this paper.